Dendrochemistry of turkey oak (Quercus cerris) in iron and manganese mining area - Jankovski, Aleksandar; Gjorevska, Ankica; Hristovski, Slavčo; Melovski, Ljupčo (Macedonian Journal of Ecology and Environment, 2012)
The results of the investigation of radial distribution of some nutrients and heavy metals (Mg, K, Ca, Na, Fe, Cu, Cd, and Mn) in the wood of Turkey Oak (Quercus cerris L.) are presented. The goal of the presented work was to analyze the radial patterns of several bioelements and heavy metals as well as to assess the impact of the iron mining and flotation pond. For that purpose, accumulation of above mentioned metals in the tree rings of oak trees in the unpolluted and affected area was analyzed. Several series of tree rings (three consecutive years as an average) were analyzed from the period of active mining (from 1950s to late 1980s). The same analysis was performed in the tree rings in the period after the mining activities were stopped.